1975
DOI: 10.1021/jo00905a024
|View full text |Cite
|
Sign up to set email alerts
|

Reductions of conjugated carbonyl compounds with cyanoborohydride in acidic media

Abstract: The reductions of a variety of conjugated aldehydes and ketones with NaBHaCN in acidic methanol and hexamethylphosphortriamide (HMPT) have been investigated. Alicyclic carbonyl compounds afforded principally the corresponding allylic alcohols in both solvents with methyl ethers as side products in methanol. The introduction of additional conjugation often resulted in reduction to allylic hydrocarbons, presumably via acid-induced ionization and hydride trapping. Formation of saturated alcohols was not observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1975
1975
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…6 It was also reported that doing of the reductions in acidic HMPT produces allylic hydrocarbons accompanied with allyl alcohols. 6 Thus, reduction of conjugated carbonyl compounds with NaBH3CN in acidic protic and aprotic solvents is not regioselective and it suffers from harsh reaction conditions (strongly acidic media) accompanied with side product formation.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…6 It was also reported that doing of the reductions in acidic HMPT produces allylic hydrocarbons accompanied with allyl alcohols. 6 Thus, reduction of conjugated carbonyl compounds with NaBH3CN in acidic protic and aprotic solvents is not regioselective and it suffers from harsh reaction conditions (strongly acidic media) accompanied with side product formation.…”
Section: Resultsmentioning
confidence: 97%
“…As seen in Table 1, NaBH3CN exhibited the best reducing capability in the presence of wet SiO2 under solvent-free conditions. However, 0.2 g wet SiO2 (100 m/m, mass ratio) which is prepared by simply mixing of water (0.1 g) and SiO 2 (0.1 g) was the requirement for complete reduction of PhCHO at room temperature or oil bath conditions (entries 5,6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[26a] 22, [30] 23, [31] 24, [32] 25, [33] 26, [34] 27, [35] 28, [36] 31-d 1 , [37] 32, [38] 33, [18] 34, [19] and 1-d 1 .…”
Section: Methodsmentioning
confidence: 99%
“…This route is distinguished by its use of the enol phosphinate (66) as precursor for the regiospecific formation of the enolate (67), which is trapped with formaldehyde, leading to hydroxymethylcyclopentenone (68). Elimination of water followed by conjugate addition of a vinylcuprate to enone (69) and subsequent elaboration of the fully functionalized cyclopentanone then completes a new total synthesis of PGF,,. Lithium di-(a-methoxyviny1)cuprate (71), another masked anion, prepared from a-methoxyvinyl-lithium, has been shown to undergo conjugate addition reactions to …”
Section: Scheme 35mentioning
confidence: 99%